Changing values, persisting cultures : case studies in value change - Halman, Loek, 1956- (European values studies (Leiden, Netherlands), 2008)
In 1981, the European and World Values surveys started the empirical investigation of cultural values on a global scale. This book builds upon the findings of these surveys and analyzes value change in various countries around the globe.